Trade, Women, Class, and Society in Ancient Western Asia - Zagarell, Allen (1986)
with comments by B. Brentjes, Michael L. Ingraham, A. Bernard Knapp, C. C. Lamberg-Karlovsky, Randall H. McGuire, Karen Brodkin Sacks, Elizabeth C. Stone, Rita P. Wright, L. M. Young and a reply by A. Zagarell.